Use of social media in disaster relief during the Kuantan (Malaysia) flood - Chong, T.; Pan, S.L.; Leong, C.; Bahri, S.; Ahmad Khan, A.F. (2014)
Natural disasters, particularly hydro-meteorological (climate-related) disasters such as droughts, tsunamis, hurricanes, typhoons and floods, have increased in prevalence and severity in recent decades. During these disasters, the most pressing relief needs are food, water, sanitation and shelter. While relief organizations are increasingly utilizing the power of social media for informational tools such as disaster response crisis mapping, social media-derived relief efforts initiated by the general public have also increased in popularity. Compared to relief organizations, which have greater access to resources, relief efforts initiated by the general public are typically less organized and more personal and exploratory in nature. This teaching case provides a detailed examination of grassroots uses of social media aimed at soliciting disaster-related assistance. The case study describes three relief effort initiatives that solicited support for victims of the most recent Malaysian flood.